Residents’ Attitude towards Tourism Impacts and Their Participation on Sustainable Tourism Development: A Case in Chiang Rai Elephant Camp, Muang Chiang Rai District, Chiang Rai Province, Thailand - Chomputima, Thippawan; Voraseyanont, Parameth; Preedatham, Kittipat; Anantanond, Sanon (วารสารการจัดการธุรกิจ มหาวิทยาลัยบูรพา, 2018)
This study aims to (1) examine level of residents’ attitude toward tourism impact and level of residents’ participation in sustainable tourism development, as well as (2) investigates how attitudes toward tourism impacts influence the residents to have participation in tourism development, particularly focus on the sustainable tourism perspective. The findings of this study revealed that level of residents’ attitude toward tourism impacts within Ruammit village were frequently interpreted as “much”. Consequently, level of residents’ participation in terms of sustainable tourism development were frequently interpreted as “sometimes”. Another finding illustrated tourism impacts have no statistical significant on the participation. The residents’ participation in Ruammit village was considered as serious obstacle for tourism development. In addition, this study also suggests that the important of residents’ participation in community development which perceived by local residents is the valued key in achieving community development. The understanding of the tourism’ impacts and how its development is being managed are need to be instructed to the residents in Ruammit village.